Islamic Education Model in Premarital Counseling: A Study at Religious Affairs Offices in Palembang - Sudharmono, Sudharmono; Zuhdiyah, Zuhdiyah; Yuniar, Yuniar; Torik, Muhammad; Wigati, Indah (AL-ISHLAH: Jurnal Pendidikan, 2026)
Premarital counseling at Religious Affairs Offices has often been implemented as an administrative and normative program rather than as a structured educational process. This study aims to construct an Islamic education model for premarital counseling at Religious Affairs Offices in Palembang, Indonesia.The study employed an embedded mixed-methods design, with qualitative inquiry as the primary approach and quantitative data as supportive evidence. Data were collected at three Religious Affairs Offices through interviews, participant observation, document analysis, questionnaires, and pretest–posttest measures involving prospective couples and program facilitators. Qualitative data were analyzed through reduction, categorization, triangulation, and thematic interpretation, while quantitative data were examined using descriptive statistics and paired comparison tests.The findings show that Islamic education in premarital counseling is constructed through three interconnected dimensions. The input dimension includes participant characteristics, facilitator competence, curriculum content, and learning facilities. The process dimension involves value-based instruction, dialogic interaction, case-based learning, experiential activities, and contextual use of learning media. The output dimension is reflected in improved participants’ understanding of Islamic marriage principles, stronger attitudes toward responsibility and mutual respect, and practical readiness in communication, conflict management, family finance, reproductive health, and religious commitment.Premarital counseling can function as a strategic site of non-formal Islamic education when it integrates theological values, adult learning principles, and practical family-life competencies. However, its effectiveness requires curriculum renewal, longer instructional duration, systematic post-counseling support, and continuous facilitator capacity-building. The proposed model offers a framework for strengthening Islamic premarital education and improving family resilience programs in Indonesia.